Fully Automated Bladder Volume Measurement System Using a T-Shaped Ultrasound Probe and Free-Hand Motion-Based 3D Reconstruction - Daehyun Park; Hyunwoo Cho; Ilseob Song; Jihun Jang; Yangmo Yoo (IEEE Access)
Accurate measurement of bladder volume is critical for the effective management of urinary diseases. Among the available modalities, ultrasound imaging is favored due to its cost-effectiveness, non-ionizing nature, and capability to provide real-time bladder volume measurements. To enhance convenience in clinical practice, ultrasound bladder scanners have been developed and adopted in various settings. However, wobbling probe devices present significant limitations, including their inability to provide real-time images, the requirement for pre-scan alignment to ensure precise probe positioning, and the necessity for multiple volume estimations to achieve measurement accuracy. Additionally, conventional image-based estimations utilizing standard ultrasound machines or recently developed bladder scanners face challenges related to the use of shape coefficients. These methods typically rely on two image planes, which fail to fully capture the bladder’s shape, resulting in considerable errors in volume estimation when compensating for shape with coefficients. To overcome these limitations, this study proposes a novel automated bladder volume measurement technique that employs a T-shaped cross-array ultrasound probe in conjunction with free-hand motion-based 3D reconstruction. The T-shaped cross-array enables the simultaneous acquisition of sagittal and transverse view images of the bladder. By moving the probe at the suprapubic region, continuously acquired sagittal images can be combined into a 3D volume, with motion compensation achieved via the transverse images. Consequently, the proposed method can accurately reconstruct the entire bladder and measure its volume without the need for shape correction coefficients, while also reducing errors associated with ultrasound probe positioning. The proposed methodology was validated through phantom experiments simulating both spherical and irregular bladder shapes. The results demonstrated an error rate ranging from -8.8% to +5.6% when compared to the ground truth, indicating the method’s high accuracy. These results indicate that the proposed method, in conjunction with the developed array and system, has the potential to reduce the necessity for catheterization in clinical settings and enhance clinical decision-making.